PERMAINAN ULAR TANGGA DALAM MENGINGKATKAN KEMAMPUAN MORAL ANAK - Eka setiawati; Mrs. Desri; Elih Solihatulmilah (Institut Pendidikan Indonesia, 2019)
Abstract - Moral religion is important to develop because it will become the basis or foundation of childrenin navigating life. From the observation of the age of 3-4 years at KOBER PGRI Bayah, it was found thatchildren's abilities in the aspects of religious moral development were relatively low. Based on the thinkingabout the factors causing the low moral capacity of the child's religion are: (1) teacher's body language is stilldifficult so that the presentation of learning is less interesting; (2) the use of methods that are less varied; (3)the lack of teaching aids owned; (4) avoiding children's interest in religious moral learning. This research usesClassroom Action Research. The results of the study show how to learn that can improve the moral capacityof religious children aged 3-4 years at KOBER PGRI Bayah, Lebak Regency. The success rate for activitiesis very significant. In the pre-cycle activities of the average percentage of 38.67% increased to 55.67% in thefirst cycle, and increased to 90.33% in the second cycle.Keywords - kemampuan moral agama, game ular tangga